1996
DOI: 10.2135/cropsci1996.0011183x003600060008x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Gain in Soybean Populations with Different Percentages of Plant Introduction Parentage

Abstract: Plant introductions (PIs) can be used to increase the genetic diversity of soybean [Glycine max (L.) Merr.] populations. A recurrent selection program was initiated to determine if populations with PI parentage would exhibit greater genetic gain for seed yield than a population with no PI parentage. The objective of our study was to evaluate the genetic gain for seed yield and correlated responses in maturity and lodging from three cycles of recurrent selection in five soybean populations, AP10 to AP14, formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 0 publications
2
28
0
1
Order By: Relevance
“…However, when soybean populations are derived from adapted and non-adapted genotypes the mean is often considered more important than the variance in determining the potential of the populations (Aschoener and Fehr, 1979;Vello et al 1984;Ininda et al 1996). It seems that there is a strong tendency for the alleles present in adapted lines to contribute to increase mean seed yield of the populations, while alleles present in non-adapted lines seem to decrease yields.…”
Section: Correlation Between Genetic Distances and Population Meansmentioning
confidence: 99%
“…However, when soybean populations are derived from adapted and non-adapted genotypes the mean is often considered more important than the variance in determining the potential of the populations (Aschoener and Fehr, 1979;Vello et al 1984;Ininda et al 1996). It seems that there is a strong tendency for the alleles present in adapted lines to contribute to increase mean seed yield of the populations, while alleles present in non-adapted lines seem to decrease yields.…”
Section: Correlation Between Genetic Distances and Population Meansmentioning
confidence: 99%
“…This may result in observations that are different from exotic germplasm (Vello et al, 1984;Ininda et al, 1996). However, as explained above, in our study the population with 50% of the parent alleles might not be the most secure option for success with selection, in spite of the high gain estimate.…”
Section: Discussionmentioning
confidence: 62%
“…One report was found for soybean (Ininda et al, 1996), but the authors used a recurrent selection program with three selection cycles to produce gain estimates of 2.8% for populations with 25% exotic germplasm, 3.1% for 50% exotic germplasm and 2.0% for 75% exotic germplasm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After three cycles of recurrent selection, Ininda et al (1996) suggested that selection of populations developed from top quality varieties continues to be the most efficient way to obtain varieties of high productivity.…”
Section: Introductionmentioning
confidence: 99%